The Effect of Work Life Quality and Work Discipline on Performance with Job Satisfaction as an Intervening Variable (Study on Employees of PT Bank Central Asia, Tbk KCU Tegal) - Safitri, Niken Lisna; Tjahjaningsih, Endang (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
PT Bank Central Asia's Tegal Branch is a private financial institution that encounters strong competition from other banks in the area. The overall performance of BCA has shown significant positive growth over the years. However, this growth does not reflect directly on the performance levels of employees at PT Bank Central Asia, Tbk in KCU Tegal. Some employees achieve outstanding scores, indicating improved performance, while others receive lower scores, suggesting a decline in their performance. Employees possessing exceptional skills contribute to better management outcomes within the organization, fostering a professional spirit among them. One way to encourage this is by enhancing the quantity of human resources. The aim of this research was to examine and outline how the quality of work life and work discipline impact performance, using job satisfaction as a middle factor. The study involved 142 employees, with a sample size of 120. Data was collected directly from participants through surveys and was analyzed through linear regression techniques. The findings indicate that both the quality of work life and work discipline significantly affect job satisfaction. Furthermore, work discipline and job satisfaction influence employee performance, but the quality of work life does not have an effect on performance at PT Bank Central Asia, Tbk at KCU Tegal. Job satisfaction effectively mediates the relationship between quality of work life and employee performance, but it does not serve as a mediator for the impact of work discipline on performance at PT Bank Central Asia, Tbk at KCU Tegal.